ANALISIS PENGEMBANGAN PENDAPATAN ASLI DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH (Studi Kasus Pemerintah Kota Tidore Kepulauan) - , Yudi Pratama Jasin, Drs. Ahmad Jamli, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was entitled An Analysis of Locally Derived Revenue Development In Support of Regional Autonomy Implementation (Case Study at Municipal Government of Tidore Archipelago). The problem limitations was taxes and levies as the largest receipt in contribution of Locally Derived Revenue. The purpose of this study was to identify and to quantify the potentialities of locally derived revenue in terms of macro and micro. The data used in this study were the primary data and the secondary data of the time series from 2007 to 2010 included the Gross Regional Domestic Product (PDRB) of Municipal Government of Tidore Archipelago as in figures and as in Local Budget (APBD). The analysis tools used in this study were elasticity calculations and mathematical calculations. Based on research results were obtained as follows: 1. Tax on non-metallic minerals and rocks, levy on port services, levy on building permit, these all kind of receipts became the revenue sources which huge potential to increase the Locally Derived Revenues. 2. Based on analysis results in macro that was the elasticity of Locally Derived Revenue (PAD) to Gross Regional Domestic Product (PDRB) was -1,01 percent. This contained a meaning that the structure of local taxes and levies were not strong, and the calculations in micro for potential taxes and levies that were The First the potentiality of tax on non-metallic minerals and rocks was Rp1.131.747.010,- per year, The Second the potentiality of levy on port services was average on Rp323.170.666,67,- per year, with the standard deviation Rp81.670.064,32,- per year, the upper bound (the optimal value) was Rp404.840.730,98,- per year, the lower bound (the pessimistic value) was Rp241.500.602,35,- per year, and The Third the potentiality of levy on building permit was average on Rp106.478.181,82,- per year, with the standard deviation Rp10.724.637,17,- per year, the upper bound (the optimal value) was Rp117.202.818,99,-per year, the lower bound (the pessimistic value) was Rp95.753.544,65,- per year.